Promotion of sexual rights and health education: knowledge of sexually transmitted infections - Guimarães, Denise Alves; Oliveira, Cândida Amélia Marinho de; Silva, Leandro César da; Gama, Carlos Alberto Pegolo da (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: The Sexually Transmitted Diseases (STD) are recognized throughout the world as an important public health problem due to their impact on people’s life quality. Objective: To survey the population knowledge of transmission ways, treatment and possible cure of some STDs and AIDS, and compare them with each other as well as with the knowledge of other diseases. Methods: An exploratory and descriptive study by the use of a questionnaire in a convenience sample composed of 403 men and women of different age groups, 252 (62.5%) women and 151 (37.5%) men. The results were compiled and analyzed by the IBM SPSS Statistics 22 software. Results: A different knowledge degree regarding the ways of transmission and prevention of STD/ AIDS was observed. Questions about AIDS had the highest right answers’ rates, above 80%. As for the transmission of certain diseases, the ones published by the media, as Aids and dengue fever, are better known and also shown high levels, above 90%. However, there was a high degree of unfamiliarity of the participants regarding those diseases not so well divulged by the health actions and government campaigns, despite their high prevalence, such as gonorrhea and syphilis. Conclusion: Information on STD and other widely disseminated diseases by the media and public health campaigns were incorporated by the participants of this research, showing the power and significance of health education campaigns.